Public Health's Next Step in Advancing Equity: Re-evaluating Epistemological Assumptions to Move Social Determinants From Theory to Practice - Golden, Tasha L.; Wendel, Monica L. (Frontiers in Public Health, 2020)
The field of public health has increasingly promoted a social ecological approach to health, shifting from an individual, biomedical paradigm to a recognition of social and structural determinants of health and health equity. Yet despite this shift, public health research and practice continue to privilege individual- and interpersonal-level measurements and interventions. Rather than adapting public health practice to social ecological theory, the field has layered new concepts (“root causes,” “social determinants”) onto a biomedical paradigm—attempting to answer questions presented by the social ecological schema with practices developed in response to biomedicine. This stymies health equity work before it begins—limiting the field’s ability to broaden conceptions of well-being, redress histories of inequitable knowledge valuation, and advance systems-level change. To respond effectively to our knowledge of social determinants, public health must resolve the ongoing disconnect between social ecological theory and biomedically-driven practice. To that end, this article issues a clarion call to complete the shift from a biomedical to a social ecological paradigm, and provides a basis for moving theory into practice. It examines biomedicine's foundations and limitations, glosses existing critiques of the paradigm, and describes health equity challenges presented by over-reliance on conventional practices. It then offers theoretical and epistemological direction for developing innovative social ecological strategies that advance health equity.